Character Makes a Difference: Where I'm From, Where I've Been, What I Believe. - Huckabee, Mike. (Nashville, TN : B & H Pub. Group, 2007)
Former Arkansas governor Mike Huckabee offers an autobiographical account of why he believes character is the key issue in everyone's life.
Preliminaries; TABLE OF CONTENTS; PART I: CHARACTER IN THE FURNACE; PART II: THE NEED FOR CHARACTER; PART III: SELECTED SPEECHES & COMMENTARY.
Description based on print version record.
Keywords: Political ethics -- United States; Christian ethics; Huckabee, Mike, -- 1955-; Arkansas -- Politics and government -- 1951-